Similar glycaemic control and less hypoglycaemia during active titration after insulin initiation with glargine 300 units/mL and degludec 100 units/mL: A subanalysis of the BRIGHT study. Issue 3 (20th December 2019) - Cheng, Alice; Harris, Stewart; Giorgino, Francesco; Seufert, Jochen; Ritzel, Robert; Khunti, Kamlesh; Lauand, Felipe; Melas‐Melt, Lydie; Westerbacka, Jukka; Bosnyak, Zsolt; Rosenstock, Julio
Abstract: Aim: To further investigate glycaemic control and hypoglycaemia in BRIGHT, focusing on the titration period. Materials and Methods: BRIGHT was a multicentre, open‐label, randomized, active‐controlled, two‐arm, parallel‐group, 24‐week study in insulin‐naïve patients with uncontrolled type 2 diabetes initiated on glargine 300 U/mL (Gla‐300) (N = 466) or degludec (IDeg‐100) (N = 463). Predefined efficacy and safety outcomes were investigated during the initial 12‐week titration period. In addition, patients' characteristics and clinical outcomes were assessed descriptively, stratified by confirmed (≤3.9 mmol/L) hypoglycaemia incidence during the initial titration period. Results: At week 12, HbA1c was comparable between Gla‐300 (7.32%) and IDeg‐100 (7.23%), with similar least squares (LS) mean reductions from baseline (−1.37% and − 1.39%, respectively; LS mean difference of 0.02; 95% confidence interval: −0.08 to 0.12). Patients who experienced hypoglycaemia during the initial titration period had numerically greater HbA1c reductions by week 12 than patients who did not (−1.46% vs. −1.28%), and higher incidence of anytime (24 hours; 73.3% vs. 35.7%) and nocturnal (00:00–06:00 hours; 30.0% vs. 11.9%) hypoglycaemia between weeks 13–24. Conclusions: The use of Gla‐300 resulted in similar glycaemic control as IDeg‐100 during the initial 12‐week titration period of the BRIGHT study, when less anytime (24 hours) hypoglycaemia with Gla‐300 versus IDeg‐100 has been reported. Experiencing hypoglycaemia shortly after initiating Gla‐300 or IDeg‐100 may be associated with hypoglycaemia incidence in the longer term, potentially impacting glycaemic management.